A dual-functional PDMS-assisted paper-based SERS platform for the reliable detection of thiram residue both on fruit surfaces and in juice. Issue 20 (11th May 2020) - Lin, Shuang; Hasi, Wuliji; Han, Siqingaowa; Lin, Xiang; Wang, Li
Abstract : A dual-functional SERS platform was developed via a paper-based substrate assisted by PDMS for measurements of thiram on fruit surfaces and in juice. Abstract : In this work, a dual-functional SERS platform was developed via a paper-based SERS substrate with the aid of hydrophobic polydimethylsiloxane (PDMS) for effective and reliable measurements of thiram on fruit surfaces and in juice. Specifically, the paper-based SERS substrate was fabricated by coating with a core–shell Au@Ag nanorod monolayer, and the SERS performance was optimized compared with multilayer adsorption. Moreover, a versatile SERS platform was constructed by simply pasting the paper-based substrate in reverse onto PDMS using polymethyl methacrylate (PMMA) tape. On the one hand, this detection platform was able to realize sample enrichment due to the excellent hydrophobicity of PDMS, thereby increasing the sensitivity of measurements, and its function was successfully displayed through the identification of thiram in orange juice. On the other hand, PDMS could also play a supporting role and the paper-based substrate reversely stuck on PDMS was able to extract samples on the side without nanoparticles, which greatly avoids damage to nanoparticles on the substrate. Therefore, the accuracy of analysis was significantly improved and the inspection of thiram on the surface of an orange was demonstrated based on this function. As a result, this proposed SERS platform provides a new strategy for preparing multifunctional SERS sensors for the on-site monitoring of chemical contaminants in the food-safety field.